PISA 2018 results: Are students smart about money? - OCDE (PISA in focus, 2020)
This May sees the release of the results from the third PISA assessment of financial literacy. These results are largely consistent with previous findings, but also go beyond earlier assessments in probing students’ behaviours and attitudes towards money matters (including digital money matters) and their exposure to financial education at school. The Covid-19 crisis has lain bare the economic and financial uncertainty and precarity that many adults face; the 15-year-old students who sit the PISA assessment will soon leave compulsory education and must take this uncertainty into account as they take decisions about further education and career pathways. Proficiency in financial literacy will help students take responsible and well-informed decisions and set them up for financial resilience later in life. Policy makers are encouraged to use the findings and recommendations in this PISA in Focus to foster enhanced financial literacy and responsible financial inclusion.
Publisher: OCDE